Herbal Medicine For Insomnia And Mental Stress/Anxiety An Expanded Evidence-Based Review Of Phytotherapeutic Interventions (The Review of Diabetic Studies, 2025)
Insomnia and anxiety disorders are among the most prevalent neuropsychiatric conditions worldwide, significantly impairing quality of life, cognitive performance, and overall health outcomes. Although conventional pharmacotherapy—including benzodiazepines, non-benzodiazepine hypnotics, and selective serotonin reuptake inhibitors (SSRIs)—remains the primary treatment approach, long-term use is frequently limited by tolerance, dependency, withdrawal phenomena, and adverse effects.Herbal medicine (phytotherapy) offers a complementary and integrative therapeutic alternative characterized by multi-target pharmacodynamics and generally favorable safety profiles. This expanded evidence-based review critically evaluates major medicinal plants with documented anxiolytic and sedative properties, including Withania somnifera, Valeriana officinalis, Passiflora incarnata, Bacopa monnieri, and Matricaria chamomilla. Mechanisms of action, phytochemical constituents, clinical trial evidence, safety considerations, and future research directions are systematically discussed. Current evidence supports their adjunctive use in mild-to-moderate insomnia and anxiety, although large-scale randomized controlled trials are still required.